Chemical Processes During Energy‐Saving Preparation of Lightweight Ceramics. Issue 6 (12th May 2014) - Kazantseva, Lidia K.; Rashchenko, Sergey V.; Colombo, P.
<x xml:space="preserve">Abstract</x> Lightweight glass‐ceramic material similar to foam glass was obtained at 700°C–800°C directly from alkali‐activated silica clay and zeolitized tuff without preliminary glass preparation. It was characterized by low bulk density of 100–250 kg/m3 and high pore size homogeneity. Chemical processes occurring in alkali‐activated silica clay and zeolitized tuff were studied using X‐ray diffraction, thermal gravimetry, IR‐spectroscopy, and scanning electron microscopy. Pore formation in both compositions is caused by dehydration of hydrated sodium polysilicates (Na2O·mSiO2·nH2O), formed during alkali activation. Additional pore‐forming gas source in alkali‐activated zeolitized tuff is trona, Na3(CO3)(HCO3)·2H2O, formed during interaction between unbound NaOH and CO2 and H2O from air. Influence of mechanical activation of raw materials on chemical processes occurring in alkaline compositions was also studied.